Eksplorasi Material Semen untuk Pengembangan Produk Elemen Estetik - I Ketut Suarna (Institut Teknologi Sains Bandung, 2020)
Cement is a unique material, initially as the base material with the mainfunction as an adhesive for other materials whose existence is always covered. Nowdays, the application of cement materials in interior elements appears to be more honest. Natural ash color and cement characteristics are interesting things to be exposed. The use of cement material has also grown not only limited to the elements that make up space (floors, walls and ceilings), but has stepped into space facilities (furniture) and aesthetic elements. Through a series of experiments with the